Symposium 3: Culture and eLearning Design: Insights from the eChina UK Programme: Symposium Introduction - Spencer-Oatey, Helen (Proceedings of the International Conference on Networked Learning, 2006)
The aim of this symposium is to explore the question How,and to what extent, may culture impact upon effective eLearning Design? The presenters are all members of the eChina UK Programme, an initiative established by the Higher Education Funding Council for England (HEFCE) and the Chinese Ministry of Education (MoE). The programme comprises a number of Sino-UK collaborative eLearning development projects, along with an overarching research project (see http://www.echinaprogramme.org ). In this symposium, culture is defined broadly, to include not only national cultures (Chinese and British), but also professional cultures (e.g. academic and technical) and different communities of practice. The first session of the symposium focuses on Chinese-UK perspectives on pedagogy in relation to eLearning design; the second session takes a project management perspective on the impact of culture on collaboration and eLearning design.